# N²-19n-92 factorise the term

2
by chopra985

2015-01-26T19:47:31+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
n²+4n - 23n-92
n (n+4) - 23(n+4)
(n-23) (n+4)
n-23=0 (or) n+4=0
n = 23 or n = -4
2015-01-26T19:49:19+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
First take the last term (-92) and split it in terms of its multiple.
-92 = -23 * 4
So make sure that when you add both the multiples you get the middle term.
-23 + 4 = -19 (middle term)
So now,
-23n+4n-92 = o
n(n-23) + 4(n-23)
(n+4) (n-23)
n = -4,23